KEPRIBADIAN PENGGUNA FACEBOOK - Anggrainy, Nur Evira; Aisa, Siti; Soleman, Aris (Institut Agama Islam Negeri (IAIN) Manado, 2024)
ABSTRACTFacebook is one of the social media that is often used to interact in cyberspace for students. The use of Facebook creates activity patterns that are divided into 4 categories, namely, electronic interactions, self-presentation, voyeurism, and gaming. Four categories of activity patterns of Facebook users can be related to the personality of individuals who use Facebook. The personality that is used to be associated with the pattern of facebook user activity is the big five personality. This study also raises the issue of the relationship between the personality of Facebook users for students in Manado City. The study used quantitative methods and the sampling technique used purposive sampling, with 250 participants. The questionnaires used are The Big Five Personality Inventory (BFI) and the Facebook Instrument Activity Pattern. The results showed that the extraversion personality trait had a significant relationship to electronic interactions and self-presentation. The personality trait of openness to experience has a significant relationship with electronic interactions, self-presentation, and voyeurism. The neuroticism personality trait has a significant relationship with voyeurism.Keywords: Personality. Pattern of Facebook Activity, and students. ABSTRAKPenelitian ini bertujuan untuk mengetahui hubungan kepribadian terhadap pola pengguna Facebook pada mahasiswa di Kota Manado. Penggunaan facebook memunculkan pola aktivitas yang terbagi atas 4 kategori yaitu, elektronic interactions, self-presentation, voyeurisme, dan gaming. Kepribadian yang digunakan untuk dihubungkan dengan pola dari aktivitas pengguna facebook yaitu the big five personality.Penelitian menggunakan metode kuantitatif dan teknik pengambilan sampel menggunakan quota sampling, dengan 250 partisipan. Kuisioner yang digunakan yakni The Big Five Personality Inventory (BFI) dan Pattern Activity Facebook Instrument. Hasil penelitian menunjukkan bahwa trait kepribadian extraversion memiliki hubungan siginifikan terhadap elektronic interactions dan self-presentation. Trait kepribadian opennes to experience memiliki hubungan signifikan terhadap elektronic interactions, self-presentation, dan voyeurisme. Trait kepribadian neuroticism memiliki hubungan signifikan terhadap voyeurisme.Kata Kunci: Kepribadian, Pola Aktivitas Pengguna Facebook, dan mahasiswa